2019
DOI: 10.1097/shk.0000000000001207
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Protects Against Barrier Dysfunction Through Maintaining Cell Surface Syndecan-1 In Vitro

Abstract: These data suggest that in-vitro, fibrinogen associated with cell surface syndecan-1 and enhanced endothelial barrier integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 31 publications
0
44
1
Order By: Relevance
“…The precise mechanism by which syndecan contributes to barrier integrity has not been well-elucidated. Our recent data demonstrated that fibrinogen (a major protein in blood) binding to sydnecan-1 on the endothelial cell surface activates the PAK1/cofilin intra-cellular signaling pathway to maintain endothelial barrier integrity 13,14 . However, much less is known about the regulation of Sdc1 expression, representing a gap in our knowledge.…”
Section: Our Results Demonstrate That Mir-19b Was Increased In Hemorrmentioning
confidence: 99%
See 3 more Smart Citations
“…The precise mechanism by which syndecan contributes to barrier integrity has not been well-elucidated. Our recent data demonstrated that fibrinogen (a major protein in blood) binding to sydnecan-1 on the endothelial cell surface activates the PAK1/cofilin intra-cellular signaling pathway to maintain endothelial barrier integrity 13,14 . However, much less is known about the regulation of Sdc1 expression, representing a gap in our knowledge.…”
Section: Our Results Demonstrate That Mir-19b Was Increased In Hemorrmentioning
confidence: 99%
“…Primary endothelial cell culture. Human lung microvascular endothelial cells (HLMEC; Lonza, MD) were cultured as we described previously 13 . miR-19b mimic and miR-19b inhibitor transfection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…fibrinogen, which is critically depleted first during bleeding [8]), TXA, and permissive hypotension along with surgical bleeding control to limit further blood loss and stabilize coagulation function pre-hospital may be an alternative as outlined in the updated European trauma guideline [9]. Protective effects to the glycocalyx and endothelial barrier integrity have been linked to the fibrinogen component rather than to plasma per se [10]. A median 3.8 g fibrinogen concentrate can increase clot stability by 5.2 mm at 5 min of viscoelastic test initiation while TXA can decrease lysis by 5.4% [11].…”
mentioning
confidence: 99%